Post-Keynesian institutionalism after the great recession - Charles J. Whalen (Levy Economics Institute of Bard College, 2012)
This paper surveys the context and contours of contemporary Post-Keynesian Institutionalism (PKI). It begins by reviewing recent criticism of conventional economics by prominent economists as well as examining, within the current context, important research that paved the way for PKI. It then sketches essential elements of PKI-drawing heavily on the contributions of Hyman Minsky - and identifies directions for future research. Although there is much room for further development, PKI offers a promising starting point for economics after the Great Recession.
Keywords: B25; B52; E12; E32; 330; Post-Keynesian Institutionalism; Institutional Economics; Post-Keynesian Economics; Financial Instability; Money-Manager Capitalism; Hyman Minsky